A configurational approach to the impact of trade fairs and trade missions on firm export activity - Joaquín Monreal-Pérez; Valeska V. Geldres-Weiss (BRQ Business Research Quarterly, 2020)
Export promotion programmes (EPPs) are argued to support firms' export activity. However, the empirical evidence for the link between EPPs and exporting is inconclusive. We argue and demonstrate by using fuzzy set methods one can uncover configurations that combine the firm's participation in specific EPPs, namely trade missions and fairs, together with certain firm-specific characteristics. We base our analysis on a sample of 641 Chilean exporters (2010-2015), and show regression results are mostly insignificant and with a much lower model fit level compared with our fuzzy set analysis. Our main findings illustrate that small, young and non-export-experienced firms gain the most from trade fairs and trade missions, which supports the notion that EPPs provide the information required in export markets.
Keywords: M16; M38; C12; 650; Export promotion programmes; Firm export activity; Trade missions; Trade fairs; Configurational approach